FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI BELAJAR ANAK USIA SEKOLAH DASAR DI MASA PANDEMI COVID-19: FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI BELAJAR ANAK USIA SEKOLAH DASAR DI MASA PANDEMI COVID-19 - Afifah, Vina Asna; Sari, Ilma Widiya (WELL BEING, 2021)
Pandemic Covid-19 had a multi-sectoral impact, including the education sector. Pandemic Covid-19 period has been running for almost 1 year in Indonesia since March 2, 2020, it makes children feel bored in online learning. There are several factors related to children's learning motivation during the Covid-19 pandemic, namely external and internal. The purpose of the study to determine the factors related the learning motivation of elementary school-aged children during Covid-19 pandemic. The research design used a cross sectional approach. The sampling technique used purposive sampling as many as 47 respondents. The results of the chi-square test of the child's age variable showed p value (0.260), child's gender (0.806), parent's age (0.504), parent's education (0.563), parent's occupation (0.192), this means p value > 0.05 means that Ha was rejected. The role of parents showed 0.003 meaning p value < 0.05 means Ha was accepted. The conclusion of this study were that the child's age factor, child's gender, parental age, parental education, parental occupation are not related of learning motivation, while the parental role factor has a significant relationship with learning motivation of elementary school age children during the Covid-19 pandemic. Further researchers were advised to examine other internal and external factors such as ideals, psychological well-being.